A citizen scientist’s survey provides insights into the movements of Atlantic and Gulf states’ populations of Black Skimmers (Rynchops niger) - Brett R. Moyer (PLoS ONE, 2026)
Ornithologists are increasingly using field readable bands—plastic rings with alphanumeric codes that are visible from a distance—to study bird populations. Because of this advance, a member of the public can now readily engage in research. On one level, such a citizen scientist can report hundreds of sightings to help the banding scientists answer their research questions. On another level, the uniquely marked birds create opportunities for that citizen scientist to conduct independent research that offers a novel perspective. I describe the results of a five-year study in Florida where I photographed 1041 bands, representing 347 Black Skimmer ( Rynchops niger ) individuals. I show that skimmers travel to Northeast Florida in large numbers from Atlantic states up to 1500 km away. In contrast, movement to NE Florida from populations along the Gulf of Mexico was limited. My encounter rate of birds from the more distant Atlantic states was nearly 20x higher than birds from Western Florida, which were as close as 275 km away. I discuss why the birds travel to NE Florida, ranging from overwintering, to staging during migration, to dispersal for breeding. I report the longest natal dispersal (281 km) for the Black Skimmer, documenting gene flow between the Gulf and Atlantic populations. The approach modeled here could be applied by citizen scientists investigating other bird species and non-avian species with field readable tags.